Study the relationship and attribution of some biomechanical javelin throw variables as an indicator to determine the efficiency of the run variables in achievement of the effectiveness of the javelin throw - khaleel Ibrahim alsudani, Atheer; Fleah Rumeeh, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to identify the values of the biomechanical throwing step variables (speed of launch, angle of departure, angle of direction, attack angle, height, spear starting point, forearm angle, upper arm angle, trunk angle , front knee angle , body mass center transmission speed) At the moment of throwing step , and on the relationship and the percentage of its contribution to achievement , where I embodied the problem of searching for the extent to which the largest mass was invested in the player ’s body to obtain the value of the momentary power, the descriptive approach was used to study relationships, and the research sample included 8 young players , and it was extracted Evaluate search variables by photographing with cameras (CASIO, 120 to 1000 images per second speed) and using kinematic analysis software. (Kinovea 8.25 The fourth chapter includes presenting, analyzing, and discussing the data results and extracting the correlation value and the contribution rate to find out which variables are more consistent with the achievement and the conclusions and values contributed to the achievement of the values of the biomechanical firing step variables (speed of launch, starting angle, angle of direction, angle of attack, height, and starting point of the spear). Forearm angle, humerus angle, trunk angle, anterior knee angle , velocity of body mass center transmission at the moment of throwing step , and either recommendations are to conduct similar research and studies on other variables, use motor analysis periodically during the identification The mechanical changes that the throwing stage takes place.